### Home > CAAC > Chapter 8 > Lesson 8.2.2 > Problem 8-58

8-58.

You can use the elimination method.

Multiply the second equation by −2.

Add the two equations together, combining like terms.

There is no solution.

−2(3*x* − *y* = 2)

−6*x* + 2*y* = − 4

6*x* − 2*y* = 10

−6*x* + 2*y* = −4

0 = 6

You can use the substitution method.

Distribute and solve for *x*.

Combine like terms.

Add 48 to both sides.

Divide by 7 on both sides.

*x* − 3(16 − 2*x*) = 1*x* − 48 + 6*x* = 1

7*x* − 48 = 1

7*x* = 49